Safety, Pharmacokinetics, & Efficacy Signals of Larsucosterol (DUR-928) in Alcohol-associated Hepatitis - Hassanein, Tarek; McClain, Craig J.; Vatsalya, Vatsalya; Stein, Lance L.; Flamm, Steven L; Martin, Paul; Cave, Matthew C.; Mitchell, Mack; Barton, Bruce; Nagy, Laura; Szabo, Gyongyi; McCullough, Arthur; et al. (The American journal of gastroenterology, 2024)
This study is to evaluate the safety and pharmacokinetics (PK) of larsucosterol (DUR-928 or 25HC3S) in subjects with alcohol-associated hepatitis (AH), a devastating acute illness without US Food and Drug Administration-approved therapies. This phase 2a, multicenter, open-label, dose escalation study evaluated the safety, PK, and efficacy signals of larsucosterol in 19 clinically diagnosed subjects with AH. Based on the model for end-stage liver disease (MELD) score, 7 subjects were considered to have moderate AH and 12 to have severe AH. All subjects received 1 or 2 intravenous infusions (72 hours apart) of larsucosterol at a dose of 30, 90, or 150 mg and were followed up for 28 days. Efficacy signals from a subgroup of subjects with severe AH were compared with those from 2 matched arms of those with severe AH treated with standard of care (SOC), including corticosteroids, from a contemporaneous study. All 19 larsucosterol-treated subjects survived the 28-day study. Fourteen (74%) of all subjects including 8 (67%) of the subjects with severe AH were discharged ≤72 hours after receiving a single infusion. There were no drug-related serious adverse events nor early terminations due to the treatment. PK profiles were not affected by disease severity. Biochemical parameters improved in most subjects. Serum bilirubin levels declined notably from baseline to day 7 and day 28, and MELD scores were reduced at day 28. The efficacy signals compared favorably with those from 2 matched groups treated with SOC. Lille scores at day 7 were <0.45 in 16 of the 18 (89%) subjects with day 7 samples. Lille scores from 8 subjects with severe AH who received 30 or 90 mg larsucosterol (doses used in phase 2b trial) were statistically significantly lower ( P < 0.01) than those from subjects with severe AH treated with SOC from the contemporaneous study. Larsucosterol was well tolerated at all 3 doses in subjects with AH without safety concerns. Data from this pilot study showed promising efficacy signals in subjects with AH. Larsucosterol is being evaluated in a phase 2b multicenter, randomized, double-blinded, placebo-controlled (AHFIRM) trial.